PROSES BUDIDAYA DAN ANALISIS KEUNTUNGAN USAHA KEPITING SANGKAK (Soft Sheel Crab) DI PENAMPUNGAN PAJA DESA ALUR DUA BARU KECAMATAN SEI LEPAN KABUPATEN LANGKAT - Fadhilah, Emma (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
In Alur Dua Baru Village, Sei Lepan District, Langkat Regency, there are many Soft Sheel Crab cultivation activities, one of those who cultivate them is Mr. Afrizal. He cultivates Soft Sheel Crab as well as containers. This shelter is named “Paja Shelter” and has been established since 2006. Soft Sheel Crab are taken from other Soft Sheel Crab farmers in the Sei Lepan District area and its surroundings. Super-sized Soft Sheel Crab are marketed to the “Toba Surimi” factory in the Medan Industrial Area (KIM) in fresh condition. Meanwhile, the medium and small sized ones are marketed to restaurants and eateries in the Medan area in frozen form. The choice of Soft Sheel Crab cultivation in “Paja Shelter” is because this business is currently developing and has great prospects. And there are still many who are not familiar with Soft Sheel Crab cultivation. Apart from that, the maritime economy (blue economy) is being promoted by the Indonesian government. The objectives of this research are: (1) To find out the process of cultivating Soft Sheel Crab; (2) To analyze the profits from the Soft Sheel Crab. Keywords: Soft Shell Crab, Cultivation, Profits